Choice-based conjoint analysis an illustration - Escuadro, Starlight Dawn C. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2014)
This paper exposes the choice-based conjoint analysis using the study on boarding house profile preferences. The analysis provides a utility value that can determine the type of boarding house preferred by the respondents. The entire process of analysis, from the making of the questionnaire to the estimation of utilities and simulation of market shares, was run through XLSTAT software. The multinomial logit estimation was used to calculate the utility values. The results showed that the respondents are more likely to live in a boarding house with the following characteristics: a monthly payment of 800php, accepts only 2 boarders per room, exclusive for male(or female), has a curfew time and has a security guard.